A Public Health Perspective on Socio-Demographic Determinants of Dental Anxiety - Sadaf Shakoor , Syed Imtiaz Ahmed Jafry , Syed Muhammad Zulfiqar Hyder Naqvi , Nazia Jameel , Syeda Nadia Firdous , Mahwish Bano (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To determine the frequency of dental anxiety and it associated factors in dental outpatients at a private tertiary care hospital of Karachi. Methods: A cross-sectional study was conducted at Baqai Institute of Health Sciences, Baqai Medical University, Karachi, from February, 2023 to December, 2024 with data collection performed at the dental outpatient department of a private tertiary care hospital of Karachi.